Hotel Reservation Management System - Ng, Chin Chien; Mohd Zaki Mohd Salikon (Applied Information Technology And Computer Science, 2022)
In this era various information and communication technologies refers to all equipment and programs that are used to process and communicate information. For example, internet has transformed the way people communicate, study, work and others daily activities. The internet is becoming popular in all the country to search the information. This study was conducted to discuss about the development of the online management system which is develop of Hotel Reservation Management System. In this system we use Waterfall Model and it involved 6 process which is requirement analysis, system design, implementation, system testing, system deployment and system maintenance to develop this system. Every phase should be following the step starting from planning phase where is we planned what will be archived in this system. This system design should be make sure the system is fully completed and functionally within the prescribed period. At the end, this system process can be used to ensure users can use this system properly and efficiently. Other than that, this system will allow customer to visit the hotel website with full access to make reservation with no extra charge. The important of using this system that will help hotel employee to manage online and walk in reservation. Besides that, customer can check the room availability based on the selected date and make reservation online. Hopefully at the end of this system will help to improve the customer experience and hotel employee work efficiency.